How User‐centric Innovation is Affecting Stakeholder Marketing Strategies: Exploratory Findings from the Music Industry. Issue 4 (3rd September 2018) - Gamble, Jordan Robert; McAdam, Rodney; Brennan, Michael
Abstract : This paper empirically explores how user‐centric innovation (UCI) in the music industry is affecting how key stakeholder groups are approaching and developing their marketing (and associated management) strategies. The three‐stage interview‐based research methodology consisted of 52 semi‐structured in‐depth interviews with UCI experts and artist managers, as well as representatives from major record labels. The findings make four substantial contributions to theory and practice in the interrelated fields of UCI, marketing and the music industry. First, they provide practical and pragmatic insights for industry practitioners on how different UCI marketing approaches are affecting their management strategies. Second, they take steps towards answering many of the identified gaps in research and knowledge relating to the concept of UCI. Third, they present theoretical models as a foundation for which new UCI marketing theory can be built upon. Last, they offer directions for future research to advance our empirical findings.